IMPROVING THE KNOWLEDGE OF DENTAL NURSES IN SUPPORTING THE IMPLEMENTATION OF THE INTEGRATED ANC PROGRAMME AT PUSKESMAS IN LAMONGAN DISTRICT - Hadi, Sunomo; Sri Hidayati; utomo, Endang Purwaningsih (Frontiers in Community Service and Empowerment, 2023)
Cross-programme cooperation between the Maternal and Child Health (MCH) room and the Dental and Oral Health room is one form of cooperation that is quite influential on the level of oral health of pregnant women. MCH which is a form of Puskesmas main activity is not only tasked with recording or knowing early all abnormalities or cases or complaints found in hard tissue and soft tissue in the oral cavity of pregnant women, but MCH also provides referral efforts to the Dental and Oral Health room for oral health care which involves the role of dentists and dental nurses. This community service aims to increase the knowledge of dental nurses in supporting integrated ANC at the Lamongan Regency Health Centre, various factors that affect the performance of dental nurses in the implementation of integrated ANC. From the results of the research, a fik performance model was found and can be taken into consideration by dental nurses in supporting the implementation of integrated ANC at the Puskesmas. The method used was to provide training for dental nurses working at Puskesmas in the Lamongan District Health Office working area, using lecture and discussion methods and questions and answers. The targets and outcomes achieved in this service are: 1) Increased knowledge of dental nurses about Ante Natal Care (ANC) and dental and oral diseases as well as systemic diseases related to pregnancy in increasing K1 visits of pregnant women at Puskesmas. This knowledge is expected to increase the visits of pregnant women to the dental clinic of the health centre. 2) Final report and article that will be included as a scientific publication in an accredited journal after the service. 3) Obtaining Haki for this module and community service. After this activity is completed, dental nurses can make efforts to increase integrated ANC visits at the Puskesmas where they work, which so far have not reached the target of visiting pregnant women in the dental clinic (Integrated ANC) not 100% so that the oral health status of pregnant women becomes better